Recurrent expressions for reliability indicators of compound electropower systems - Sydor, A.R.; Teslyuk, V.M.; Denysyuk, P.Yu. (Технічна електродинаміка, 2014)
Main reliability indicators of unrestorable compound electropower systems are examined in this paper. A method of investigation of reliability indicators for compound electropower systems by means of generating functions is developed taking account of aging of the system’s output elements. Recurrent expressions are worked out for the failure probability in the prescribed availability condition, the failure frequency in the prescribed availability condition and the failure rate in the prescribed availability condition provided that the lifetime of ageing output elements is described by the Rayleigh distribution. В статье рассматриваются основные показатели надежности невосстанавливаемых сложных электроэнергетических систем. Метод исследования показателей надежности сложных электроэнергетических систем с помощью производящих функций распространен на случай старения выходных элементов системы. Разработаны рекуррентные выражения для вероятности отказов при заданном условии готовности, частоты отказов при заданном условии готовности и интенсивности отказов при заданном условии готовности для случая, когда безотказность стареющих выходных элементов описывается распределением Релея. Розглянуто основні показники надійності невідновлюваних складних електроенергетичних систем. Метод дослідження показників надійності складних електроенергетичних систем за допомогою твірних функцій поширено на випадок старіння вихідних елементів системи. Розроблено рекурентні вирази для ймовірності відмов за заданої умови готовності, частоти відмов за заданої умови готовності та інтенсивності відмов за заданої умови готовності для випадку, коли безвідмовність старіючих вихідних елементів описується розподілом Релея.